1991
DOI: 10.7164/antibiotics.44.925
|View full text |Cite
|
Sign up to set email alerts
|

Structure of aureobasidin A.

Abstract: Aureobasidin A, a new antifungal antibiotic, was isolated from the culture mediumof Aureobasidium pullulans R106. Aureobasidin A was a cyclic depsipeptide consisting of eight a-amino acid units and one hydroxy acid unit. The structures of the units were found by acid hydrolysis of the antibiotic to be 2 and L-phenyl-alanine. The sequence of the units was identified by NMRand FAB-MSof the products from the alkaline hydrolysis of aureobasidin A. 925Aureobasidins are complexes of antifungal antibiotics produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 12 publications
3
60
0
1
Order By: Relevance
“…As shown in Fig. 1A, AbA strongly inhibits the growth of filamentous fungi such as A. oryzae, P. oxalicum, and Acremonium sp., previously reported for the yeast Saccharomyces cerevisiae (W303-1A) and other fungi (7)(8)(9)(10)13). However, growth inhibition by AbA was not observed for any Zygomycetes species such as M. hiemalis, R. microsporus, R. pusillus, and A. corymbifera (Fig.…”
Section: Growth Of Fungi Resistant Tomentioning
confidence: 73%
See 1 more Smart Citation
“…As shown in Fig. 1A, AbA strongly inhibits the growth of filamentous fungi such as A. oryzae, P. oxalicum, and Acremonium sp., previously reported for the yeast Saccharomyces cerevisiae (W303-1A) and other fungi (7)(8)(9)(10)13). However, growth inhibition by AbA was not observed for any Zygomycetes species such as M. hiemalis, R. microsporus, R. pusillus, and A. corymbifera (Fig.…”
Section: Growth Of Fungi Resistant Tomentioning
confidence: 73%
“…We found that all Zygomycetes species tested were resistant to the antifungal agent Aureobasidin A, a cyclic depsipeptide produced by Aureobasidium pullulans (10). The Zygomycetes species do not have inositol-containing sphingolipids but contain novel neutral glycosphingolipids (GSLs) consisting glucose or galactose as sugar constituents.…”
mentioning
confidence: 99%
“…During our search for peptide antibiotics which interact with human Pgp, we found that Saccharomyces cerevisiae expressing human MDRllPgp showed resistance to aureobasidin A, a new antifungal cyclic depsipeptide antibiotic produced by Aureobasidium pullulans R106 [15,16]. Surprisingly the overexpression of MDR2/Pgp also conferred resistance to aureobasidin A.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were grown in YPD medium containing 0.5mg/ml of AbA [11] at 30 o C. Each samples treated with zymolyase 20T, then cells were homogenized and fractionated into mitochondrial [12] or post-mitochondrial fractions by using the centrifugation method as described in Methods section; the latter was usually used as the starting material for Unfold in preparation (Figure 1). In these experiments, mitochondrial and postmitochondrial samples were firstly examined using two column chromatography steps, Ni-NTA and ion exchange chromatography, followed by gel filtration chromatography, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The gene was fused at the C-terminal with hexahistidine-tag then amplified by PCR and then inserted into aureobasidine A (AbA) selective expression vector pAUR123 [11] (Takara BioChemicals). The protease-deficient yeast strain BY2778 [MATα prb1 -D1.6R pep4::HIS3 ura-3-52 his3-D200 can1 gal2] was transformed with this plasmid, grown in YPD medium containing 0.5 mg/ml of AbA at 30 o C. Cells were collected and treated with 2.5 mg/ml of zymolyase 20T then homogenized using glass pestle downs homogenizer.…”
Section: Purification Of Hexahistidine-tagged Unfoldinmentioning
confidence: 99%